Implementación de un módulo didáctico multifuncional para la asignatura de electrónica de potencia - Flores Jacome, Evelin Valeria (2022)
The present project is based on the implementation of a multifunctional didactic module for the subject of power electronics, it is composed of circuits where the current transformations studied in the subject are identified. The first module is a variable source that transforms alternating energy into direct energy, to measure their waveforms and identify the differences and their behavior; the second module is the PWM circuit that conserves its continuous energy, this main component has a maximum voltage of 30 volts and a minimum voltage of 0. 64 volts, its square shape can be identified using the oscilloscope; the third module is an inverter circuit whose function is to transform a direct current into an alternating current, it enters a voltage of 12 volts and as output will have a voltage of 110 volts, all energy conversion will be observed in the measuring instrument; the fourth module is a phase control circuit, this will vary the pulse width in a full wave.